Teaching Advanced Business English Writing Skills in the Digital Environment - Valentina BUDINČIĆ (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Due to the huge increase in written communication over recent decades, improving writing skills in foreign language has become one of the particularly important questions in ELT methodology. This paper elaborates on writing as one of the foremost communication skills in business context and investigates teaching models and techniques which can be efficiently employed in advanced Business English language courses in the digital environment. The aim of this paper is to propose some ideas on how to enhance learning and teaching writing skills particularly focusing on the online platforms which provide a rich variety of tools and resources for all participants in advanced Business English courses.